2015
DOI: 10.3109/02699052.2015.1024740
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary psychometric evaluation of the interpersonal communication competence scale for aquired brain injury

Abstract: The ICCS-Staff/Relative revealed a good overall internal consistency, whereas the ICCS-Self-rating revealed acceptable internal consistency. The factor analysis of the proxy-rating revealed six meaningful sub-groups of interpersonal communication competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…This is similar to other sample sizes used in testing the measurement properties of scales about responsive to various music conditions (e.g. Clark, Baker, Peiris, Shoebridge, & Taylor, 2015;Hald, Baker, & Ridder, 2015;Magee, Siegert, Taylor, Daveson, & Lenton-Smith, 2016) and comparable with the acute psychiatric sample in an earlier validation of the MSS (Baker et al, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…This is similar to other sample sizes used in testing the measurement properties of scales about responsive to various music conditions (e.g. Clark, Baker, Peiris, Shoebridge, & Taylor, 2015;Hald, Baker, & Ridder, 2015;Magee, Siegert, Taylor, Daveson, & Lenton-Smith, 2016) and comparable with the acute psychiatric sample in an earlier validation of the MSS (Baker et al, 2016).…”
Section: Discussionsupporting
confidence: 74%
“…In their initial studies, Rubin and Martin (1994) found good reliability, validity and internal consistency of the ICCS. The ICCS has been incorporated successfully into a range of psychology, communication and leadership studies (Macik-Frey, 2007;Anders & Tucker, 2000;Fields, 2008;Chan, 2003), with good reliability and validity in a range of samples (Puggina & Da Silva, 2014;Hald, Baker & Ridder, 2015;Rubin & Martin, 1994). As scored, higher scores for each domain indicate higher levels of communication.…”
Section: Communicationmentioning
confidence: 99%
“…The measure chosen for this study is the Interpersonal Communication Competency Scale [12], [27]- [30]. It was chosen because it is the most comprehensive measure of interpersonal communication competence and provides a better operationalization of the global construct.…”
Section: Instrumentmentioning
confidence: 99%